Identity and cultural diversity in the construction of knowledge on the program of Education Postgraduate of the Universidade Federal do Amazonas - Brito, Rosa Mendonça de (2015)
The study presented here aimed to capture, interpret and understand the processes of construction of knowledge developed by the postgraduate program in education of UFAM. The plunge in their doings, in society and culture in which itis inserted, was accomplished through a case study involving theoretical research, empirical documents and guided by five main issues. The qualitative analysis of data-raised through observations and interviews-had as a guide the principles of phenomenology, hermeneutics and the dialogical and inallowed to seize the immense plot and the network of meanings weaved by energy that emerges from life of the Amazon and its world subjects which transcend, in lot, the pure logical relationships beams where humans are treated as clones, doomed to an eternal repetition. The analysis articulated perceptions of the researchers and the subjects involved with empirical research and theoretical conceptions, have revealed the richness and fertility of the Amazonian cultures and the direction of the program, which has its support in local insertion in the context with universal and hence complies fully with its function to qualify professionals for superior teaching and build knowledge that value and encouragein an intersubjective and intercultural perspective, dialogue between the different knowledges.